Hetero-cycloreversions Mediated by Photoinduced Electron Transfer - Pérez-Ruiz, Raúl; Jiménez, M. Consuelo; Miranda, Miguel A (Accounts of chemical research, 2014)
Discovered more than eight decades ago, the Diels–Alder (DA) cycloaddition (CA) remains one of the most versatile tools in synthetic organic chemistry. Hetero-DA processes are powerful methods for the synthesis of densely functionalized six-membered heterocycles, ubiquitous substructures found in natural products and bioactive compounds. These reactions frequently employ azadienes and oxadienes, but only a few groups have reported DA processes with thiadienes. The electron transfer (ET) version of the DA reaction, though less investigated, has emerged as a subject of increasing interest. In the last two decades, researchers have paid closer attention to radical ionic hetero-cycloreversions, mainly in connection with their possible involvement in the repair of pyrimidine(6–4)pyrimidone photolesions in DNA by photolyases. In biological systems, these reactions likely occur through a reductive photosensitization mechanism. In addition, photooxidation can lead to cycloreversion (CR) reactions, and researchers can exploit this strategy for DNA repair therapies. In this Account, we discuss electron-transfer (ET) mediated hetero-CR reactions. We focus on the oxidative and reductive ET splitting of oxetanes, azetidines, and thietanes. Photoinduced electron transfer facilitates the splitting of a variety of four-membered heterocycles. In this context, researchers have commonly examined oxetanes, both experimentally and theoretically. Although a few studies have reported the cycloreversion of azetidines and thietanes carried out under electron transfer conditions, the number of examples remains limited. In general, the cleavage of the ionized four-membered rings appears to occur via a nonconcerted two-step mechanism. The trapping of the intermediate 1,4-radical ions and transient absorption spectroscopy data support this hypothesis, and it explains the observed loss of stereochemistry in the products. In the initial step, either C–C or C–X bond breaking may occur, and the preferred route depends on the substitution pattern of the ring, the type of heteroatom, and various experimental conditions. To better accommodate spin and charge, C–X cleavage happens more frequently, especially in the radical anionic version of the reaction. The addition or withdrawal of a single electron provides a new complementary synthetic strategy to activate hetero-cycloreversions. Despite its potential, this strategy remains largely unexplored. However, it offers a useful method to achieve CX/olefin metathesis or, upon ring expansion, to construct six-membered heterocyclic rings.